Isolated heart transplantation for familial transthyretin (TTR) V122I cardiac amyloidosis. (June 2014) - Thenappan, Thenappan; Fedson, Savitri; Rich, Jonathan; Murks, Catherine; Husain, Aliya; Pogoriler, Jennifer; Anderson, Allen S.
Abstract Transthyretin (TTR) cardiac amyloidosis is characterized by deposition of either mutant or wild type TTR amyloid protein in the myocardium ultimately leading to progressive cardiomyopathy and heart failure. The most common TTR gene mutation that leads to TTR cardiac amyloidosis is the valine-to-isoleucine substitution at position 122 (V122I or Ile122). Currently, the only definitive treatment suggested for mutant TTR cardiac amyloidosis is the combined or sequential liver-heart transplantation in eligible patients, since liver is the source of TTR production. Here, we report a case of heterozygous Val122L mutated TTR-related cardiac amyloidosis treated with isolated heart transplantation with no recurrence of amyloid in the cardiac allograft and no systemic abnormalities 5 years after heart transplantation. <glossary> <def-list> Abbreviations <def-item> <term id="G1">MMF</term> <def> mycophenolate mofetil </def> </def-item> <def-item> <term id="G2">NYHA</term> <def> New York Heart Association </def> </def-item> <def-item> <term id="G3">TTR</term> <def> transthyretin </def> </def-item> <def-item> <term id="G4">VE</term> <def> minute ventilation </def> </def-item> </def-list> </glossary>